2021
DOI: 10.21037/jgo-20-337
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models for stage I–III esophageal cancer: a comparison between existing calculators

Abstract: Background: Determining the best approach for esophageal cancer and predicting accurate prognosis are critical. Multiple studies evaluated characteristics associated with overall survival, and several prediction models have been developed. This study aimed to evaluate existing models and perform external validation of selected models.Methods: A retrospective investigation of a multi-site institutional enterprise for patients with a diagnosis of esophageal cancer between 2013-2014 was performed. Selected surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…Recurrence was often encountered after radical resection of ESCC and greatly affected the prognosis of patients ( 23 ). Unlike the effect of predicting OS and PFS ( 7 , 8 ), we found that TNM staging of primary tumor was not significantly associated with PPS in univariate analysis, suggesting that TNM staging was not effective in predicting PPS in ESCC patients. Similar to our conclusions, many studies on PPS of other cancer types suggested that the TNM staging system was less useful to predict the PPS prognosis ( 24 , 25 ).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Recurrence was often encountered after radical resection of ESCC and greatly affected the prognosis of patients ( 23 ). Unlike the effect of predicting OS and PFS ( 7 , 8 ), we found that TNM staging of primary tumor was not significantly associated with PPS in univariate analysis, suggesting that TNM staging was not effective in predicting PPS in ESCC patients. Similar to our conclusions, many studies on PPS of other cancer types suggested that the TNM staging system was less useful to predict the PPS prognosis ( 24 , 25 ).…”
Section: Discussioncontrasting
confidence: 87%
“…Currently, several models have been showed to predict postoperative OS and progression-free survival (PFS) for EC by using primary tumor characteristics ( 7 , 8 ). Whereas, compared to OS and PFS, the survival after relapse of EC patients may be influenced by characteristics of the primary tumor as well as the recurrence-related features, such as recurrence patterns, metastatic sites, and recurrence interval ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lemini R et al. ( 21 ) further externally validated several currently existing prognostic prediction models for the patients with esophageal adenocarcinoma. Unfortunately, none of these models showed satisfactory prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the discrimination of the CoxPH model was slightly improved (0.755), which may be related to the fact that we included more cases. The algorithm proposed by Shapiro ( 33 ) progressed under predicting 1-year survival, with an AUC of 0.63 in the internal validation dataset ( 34 ). Although our DeepSurv model slightly outperformed the Shapiro algorithm in predicting 1-year survival (AUC of DeepSurv: 0.828), what makes our study more significant is that using the deep feed-forward neural network algorithm.…”
Section: Discussionmentioning
confidence: 99%